ABCB1 4036A>G and 1236C>T Polymorphisms Affect Plasma Efavirenz Levels in South African HIV/AIDS Patients - Swart, Marelize; Ren, Yuan; Smith, Peter; Dandara, Collet (Frontiers in Genetics, 2012)
Abstract The ABCB1 gene encodes P-glycoprotein, an ATP-dependent drug efflux pump, which is responsible for drug transport across extra- and intra-cellular membranes. The variability in the expression of ABCB1 may contribute to variable plasma efavirenz concentration which results in variability in the levels of suppression of the human immunodeficiency syndrome virus (HIV). The aim of the study was to evaluate the role of polymorphisms in ABCB1 gene on plasma efavirenz levels and treatment response in the form of change in viral load and CD-4 cell count in HIV/AIDS patients receiving efavirenz-containing HAART regimens. 301 HIV-infected patients were recruited from Themba Lethu Clinic in Johannesburg and plasma efavirenz drug concentration levels were measured using LC-MS/MS. SNaPshot was used to genotype five known ABCB1 SNPs. Genotype-phenotype correlations were computed. The ABCB1 4036A/G and 4036G/G genotypes were significantly associated with low plasma efavirenz concentrations (P=0.0236), while the ABCB1 1236C/T and 1236T/T genotypes were associated with high efavirenz concentrations (P=0.0282). A haplotype ABCB1 T-G-T-A is reported that is associated with significantly increased plasma efavirenz levels. This is the first report on 61A>G, 2677G>T/A and 4036A>G SNPs in the South African population. ABCB1 plays a role in determining the plasma concentrations of efavirenz and should be taken into account in future design of assays for genotype-based dosing of efavirenz-containing regimens.